Regulation of two-pore-domain potassium TREK channels and their involvement in pain perception and migraine. (16th March 2022) - Ávalos Prado, Pablo; Chassot, Anne-Amandine; Landra-Willm, Arnaud; Sandoz, Guillaume
Highlights: TREK channels are involved in pain perception. TREK channel heteromerization is involved in migraine. TREK channels regulate sensory neuron excitability. TREK channels as targets for pain and migraine treatment. Abstract: The ability to sense pain signals is closely linked to the activity of ion channels expressed in nociceptors, the first neurons that transduce noxious stimuli into pain. Among these ion channels, TREK1, TREK2 and TRAAK from the TREK subfamily of the Two-Pore-Domain potassium (K2P ) channels, are hyperpolarizing channels that render neurons hypoexcitable. They are regulated by diverse physical and chemical stimuli as well as neurotransmitters through G-protein coupled receptor activation. Here, we review the molecular mechanisms underlying these regulations and their functional relevance in pain and migraine induction.